Pembuatan Dem Dari Sumber Data Citra Aster - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Energi UGM, 2005)
ABSTRAK AM-1 (Terra) satellite that carries ASTER sensor having 15 m spatial resolution. It has capability to record the same area from different exposure station along satellite orbit, so that it can produce stereoscopic model and provide height information. This paper will evaluate the accuracy of height information provided by ASTER image. Parallax differences of conjugate points concept was implemented to determine height data. While conjugate points were determined using one of the area based image matching techniques called cross correlation approach. The computed height furthermore were compared to the observed height from 1:25000 topographic map. A pair of ASTER images covering part of the Tuban area was used in this investigation. By using 150 sample points, it provides 8,8 m RMS of the height differences.